Foundations and practice of security : 11th International Symposium, FPS 2018, Montreal, QC, Canada, November 13-15, 2018, Revised selected papers /: 11th International Symposium, FPS 2018, Montreal, QC, Canada, November 13-15, 2018, Revised selected papers. (2019) - Unknown
No abstract available